Institutional setting for nature-based solutions and REDD+ policies and projects in Viet Nam - Pham, T.T.; Vu, T.P.; Nguyen, T.M.L.; Hoang, T.L.; Trần Ngọc, M.H. (Center for International Forestry Research, 2022)
This report identifies the drivers of deforestation and degradation in Vietnam, and then analyses aspects of the social, political and institutional context that might constrain or support the design and implementation of REDD+ in Vietnam. The study also aims to increase understanding of the national and provincial governing bodies, how they interact, their knowledge and capacity to engage in and implement REDD+ and identify gaps in stakeholders’ capacity to implement REDD+. The recommendations contained in this report are intended for project investors and organizations who have interest in developing and implementing emission reduction and REDD+ projects in Vietnam.